Direct and Indirect Determination of the Magnetocaloric Effect in the Heusler Compound Ni1.7Pt0.3MnGa - Ricardo D. dos Reis; Luana Caron; Sanjay Singh; Claudia Felser; Michael Nicklas (Entropy, 2021)
Magnetic shape-memory materials are potential magnetic refrigerants, due the caloric properties of their magnetic-field-induced martensitic transformation. The first-order nature of the martensitic transition may be the origin of hysteresis effects that can hinder practical applications. Moreover, the presence of latent heat in these transitions requires direct methods to measure the entropy and to correctly analyze the magnetocaloric effect. Here, we investigated the magnetocaloric effect in the Heusler material Ni<semantics>1.7</semantics>Pt<semantics>0.3</semantics>MnGa by combining an indirect approach to determine the entropy change from isofield magnetization curves and direct heat-flow measurements using a Peltier calorimeter. Our results demonstrate that the magnetic entropy change <semantics>ΔS</semantics> in the vicinity of the first-order martensitic phase transition depends on the measuring method and is directly connected with the temperature and field history of the experimental processes.